The Mitochondrial Genome Integrity Gene, Mgi1, of Kluyveromyces Lactis Encodes the β-Subunit of F(1)-Atpase - Chen, X. J. (1996)
In a previous report, we found that mutations at the mitochondrial genome integrity locus, MGI1, can convert Kluyveromyces lactis into a petite-positive yeast. In this report, we describe the isolation of the MGI1 gene and show that it encodes the β-subunit of the mitochondrial F(1)-ATPase. The site of mutation in four independently isolated mgi1 alleles is at Arg435, which has changed to Gly in three cases and Ile in the fourth isolate. Disruption of MGI1 does not lead to the production of mitochondrial genome deletion mutants, indicating that an assembled F(1) complex is needed for the ``gain-of-function'' phenotype found in mgi1 point mutants. The location of Arg435 in the β-subunit, as deduced from the three-dimensional structure of the bovine F(1)-ATPase, together with mutational sites in the previously identified mgi2 and mgi5 alleles, suggests that interaction of the β- and α- (MGI2) subunits with the γ-subunit (MGI5) is likely to be affected by the mutations.